Fear of Missing Out as a Mediator Between Live Streaming, Twin Dates, and Student Shopping Behavior - Muhammad Furqan; Mahendra Adhi Nugroho (International Journal of Economics and Management Sciences, 2025)
The development of e-commerce and digital technology has changed the consumption patterns of students, especially through live streaming features and twin date events on Shopee. This study aims to analyze the role of Fear of Missing Out (FOMO) in mediating the influence of live streaming and twin-date events on the consumption behavior of students at Yogyakarta State University. A quantitative approach was used with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The research sample consisted of 315 student respondents who had used the live streaming feature and participated in Shopee's twin-date events. The results showed that twin-date events had a positive and significant effect on FOMO and consumer behavior, while live streaming only had a significant effect on consumer behavior but not on FOMO. FOMO itself significantly influences consumer behavior and mediates the influence of the twin date event on consumer behavior. However, FOMO does not mediate the influence of live streaming on consumer behavior. This finding indicates that the urgency of time and exclusive promotions during the twin date event are more effective in triggering FOMO than live streaming. This study recommends the importance of digital consumption literacy for students and the development of emotion-based marketing strategies by e-commerce platforms. This study has limitations in terms of sample scope and variables used, so further research is recommended to include additional variables such as lifestyle or financial literacy, and to expand the sample to other universities.